2001
DOI: 10.1530/eje.0.1440087
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of glucocorticoid metabolism by 11beta-hydroxysteroid dehydrogenases in target tissues

Abstract: 11b-Hydroxysteroid dehydrogenases (11b-HSD) are microsomal enzymes that catalyze the conversion of active glucocorticoids (GC) to their inactive 11-dehydro products and vice versa. Two isoenzymes of 11b-HSD have been characterized and cloned in human tissues. The tissue-specific metabolism of GC by these enzymes is important for mineralocorticoid (MC) and GC receptor occupancy and seems to play a crucial role in the pathogenesis of diseases such as apparent MC excess syndrome, and may play roles in hypertensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 128 publications
1
27
0
1
Order By: Relevance
“…A second PPAR-␥Ϫmodulated pathway that has been shown to be responsible for adipose tissue homeostasis involves the enzyme 11␤-HSD-1 (23), which locally converts inactive corticosteroids into potent glucocorticoid receptor agonists (41,42). Here we found that PPAR-␥ agonist treatment caused 11␤-HSD-1 expression to be greatly diminished in VF, but not in SF.…”
Section: Discussionmentioning
confidence: 65%
“…A second PPAR-␥Ϫmodulated pathway that has been shown to be responsible for adipose tissue homeostasis involves the enzyme 11␤-HSD-1 (23), which locally converts inactive corticosteroids into potent glucocorticoid receptor agonists (41,42). Here we found that PPAR-␥ agonist treatment caused 11␤-HSD-1 expression to be greatly diminished in VF, but not in SF.…”
Section: Discussionmentioning
confidence: 65%
“…Since the in vivo anti-MC effect of progesterone seems to be moderate, we hypothesized that progesterone is metabolized by enzymes of hMR target tissues similar to the way cortisol is metabolized by 11b-HSD-2 to protect the hMR (10,19). We identified a potent and efficient enzyme system in male and in pre-and postmenopausal human kidneys (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…hMR exhibits almost the same affinity for the mineralocorticoid (MC) aldosterone, the glucocorticoid cortisol and the progestogen progesterone (6 -9). In vivo, cortisol is prevented from binding to hMR by the enzyme 11b-hydroxysteroid dehydrogenase type 2 (11b-HSD-2), which converts cortisol to its inactive metabolite cortisone in hMR target cells (10). This enzyme-mediated specificity of hMR was first described by Funder et al (11) and Edwards et al in 1988 (12).…”
Section: Introductionmentioning
confidence: 99%
“…Further, pregnant mothers threatening preterm birth (~7-10% of all pregnancies), receive antenatal glucocorticoids, to mature the lungs of the fetus prior to birth to reduce neonatal morbidity and mortality [25]. As for cortisol, synthetic glucocorticoids can be catalysed by 11 HSD2, however they are a poor substrate for the enzyme, and more freely cross the placenta than cortisol [33]. The presence of excess maternal glucocorticoids can have positive effects on fetal development and maternal health and in many situations cannot be avoided.…”
Section: Exposure To Synthetic Glucocorticoidsmentioning
confidence: 99%